Physicochemical and Perceived Olfactory Changes in Black Soldier Fly (Hermetia illucens) Larvae Oil Under Domestic Cooking Temperatures - Kian Aun Chang; Sze Ying Leong; Lye Yee Chew; Ching Qi Lim; Meng Jack Lim; Zongwei Ong; Sook Wah Chan (Foods, 2025)
The rapid growth and sustainable production of black soldier fly larvae (BSFL) contribute positively to the circular economy. This study profiled the fatty acid composition of crude BSFL oil, followed by an evaluation of its physicochemical properties under domestic cooking temperatures (up to 180 °C, 30 min). Odour evaluation of the BSFL oil was also performed using 10 trained panellists for attributes such as fishy, nutty, oily, meaty/savoury, roasted, and pungent. The results indicated that BSFL oil contains palmitic (23.69%), oleic (30.90%), and linoleic (21.81%) acids in relatively similar proportions, representing a mix of saturated, monounsaturated, and polyunsaturated fatty acids. Heating caused BSFL oil to be darker and more viscous. The peroxide and free fatty acid values also increased significantly (p < 0.05) with rising temperatures, indicating limited oxidative stability and reduced suitability of BSFL oil for cooking purposes. The perceived intensity of odour attributes, particularly fishy and oily notes, increased concomitantly with higher cooking temperatures. Refining processes and antioxidants may assist in improving the thermal stability of BSFL oil for culinary applications.